Type of Atrial Fibrillation and Clinical Outcomes in Patients Undergoing Transcatheter Aortic Valve Replacement. Issue 5 (28th January 2016) - Shaul, Aviv A.; Kornowski, Ran; Bental, Tamir; Vaknin‐Assa, Hana; Assali, Abid; Golovchiner, Gregory; Kadmon, Ehud; Codner, Pablo; Orvin, Katia; Strasberg, Boris; Barsheshet, Alon
Abstract : Background: There are limited data available regarding the relationship between atrial fibrillation (AF) clinical type, oral anticoagulation (OAC) treatment, and clinical outcome after transcatheter aortic valve replacement (TAVR). The study was designed to evaluate this relationship. Methods: We analyzed data from the Rabin Medical Center TAVR registry, including 319 consecutive patients who underwent TAVR from 2008 to 2014. Patients were divided into three groups based on their history of AF: sinus rhythm (SR), paroxysmal AF (PAF), or nonparoxysmal AF (NPAF). Results: There were 211 (66%), 56 (18%), and 52 (16%) patients in the SR, PAF, and NPAF groups, respectively. The cumulative risk for stroke or death at 2 years was highest among patients with NPAF (38%), but similarly low in PAF (15%) and SR patients (16%, P < 0.001). By multivariate analysis, patients with NPAF demonstrated a significantly higher risk of stroke or death (HR = 2.76, 95% CI 1.63‐4.66, P < 0.001), as compared with SR. In contrast, patients with PAF had a similar risk of stroke or death compared with SR (HR = 0.80, P = 0.508). Patients with NPAF not treated with OAC demonstrated an 8.3‐fold (P < 0.001) increased risk of stroke or death, whereas patients with PAF not treated with OAC had a similar risk of stroke or death compared with the SR group (HR = 1.25, P = 0.569). Conclusion: History of NPAF, but not PAF, is associated with a significant increased risk of stroke or death compared with sinus rhythm in patients undergoing TAVR.